1995
DOI: 10.1007/bf01409603
|View full text |Cite
|
Sign up to set email alerts
|

The career development of black and white South African university students

Abstract: Abstract. This study investigates the possible influence of gender and culture on the career maturity and study and work role salience of South African students. Responses to the Life Role Inventory and Career Development Questionnaire of 260 first-year university students (137 white, 123 black) were analyzed. Culture was found to have a significant effect on both career maturity and study and work role salience while gender had no significant effect. Results are related to previous findings from international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…Previous studies have shown that the SI is reliable and valid (Duarte, 1995;Farmer, 1983;Luzzo, 1994;Munson, 1992;Nevill & Super, 1986b;Perrone et al, 2006;Watson et al, 1995). To be considered a useful measure for the Brazilian population, the Brazilian version of the SI should also display adequate reliability and validity and the present study provides evidence of this.…”
Section: Confi Dencesupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have shown that the SI is reliable and valid (Duarte, 1995;Farmer, 1983;Luzzo, 1994;Munson, 1992;Nevill & Super, 1986b;Perrone et al, 2006;Watson et al, 1995). To be considered a useful measure for the Brazilian population, the Brazilian version of the SI should also display adequate reliability and validity and the present study provides evidence of this.…”
Section: Confi Dencesupporting
confidence: 57%
“…Perrone et al (2006) used the Commitment subscales for the Work, and Home and Family roles when studying the work-family interface and life satisfaction with 154 college students, married and employed full-time, fi nding good internal consistency indices (Cronbach's alpha) of 0.89 and 0.95 respectively. Other studies, such as Luzzo (1994), Munson (1992), and Watson, Stead and De Jager (1995) presented similar levels of internal consistency.…”
mentioning
confidence: 67%
“…For example, Creed and Patton (2003) found gender to be a significant correlate with career develop-ment knowledge, work commitment, indecision, and school commitment. Other studies have shown gender differences for career maturity, with some showing women being more mature (Fouad, 1988;Luzzo, 1995;Rojewski, Wicklein, & Schell, 1995) and other studies failing to show any differences for gender (Kelly & Colangelo, 1990;Watson, Stead, & De Jager, 1995). An additional purpose of the current study was to focus specifically on freshmen outcomes.…”
mentioning
confidence: 90%
“…Versões adaptadas e normatizadas deste inventário foram utilizadas com sucesso em outros países, notadamente no Canadá (Dupont & Marceau, 1982), na Espanha (Moreno, 1987), na Áustria (Seifert & Eder, 1985), na África do Sul (Watson, Stead & Jager, 1995), na Suíça (Descombes, Frischknecht, Dupont & Huter, 1977), em Portugal (Ferreira & Caeiro, 1981), na Austrália (Punch & Sheridan, 1985) e na Inglaterra (Ward, 1982). Entretanto, os resultados obtidos nestes estudos, os quais foram favoráveis, não parecem ter tido continência no caso do Brasil (Fernandes & Scheeffer, 1986;Scheeffer & Fernandes, 1984) e nos Países Baixos (Helbing, 1984) onde os resultados não puderam permitir conclusões positivas quanto a sua utilização na população adolescente.…”
Section: Pesquisas Em Outros Países Com O CDIunclassified